2009
DOI: 10.1097/mop.0b013e3283292629
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards making social toxins mainstream in children's environmental health

Abstract: Purpose of Review-While traditional disciplinary research theory and methods have focused separately on how social and physical environmental factors affect children's health, evolving research underscores important integrated effects.Recent findings-This review outlines the specific reasons why social determinants should be considered mainstream in children's environmental health research with particular focus on interactive effects between social and physical hazards. These include (a) sensitivity of overlap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 94 publications
(74 reference statements)
1
54
0
2
Order By: Relevance
“…A concept has been put forward suggesting the social contexts in which children are raised is just as detrimental to their development as physical environmental factors are. 45 It is also possible that epigenetic programming may cause long-lasting alterations in stressinduced phenotypic plasticity related to asthma risk. 46 There are frequent reports that nonwhite children living in poverty and residing in urban areas have a significantly higher risk of asthma than white children.…”
Section: Discussionmentioning
confidence: 99%
“…A concept has been put forward suggesting the social contexts in which children are raised is just as detrimental to their development as physical environmental factors are. 45 It is also possible that epigenetic programming may cause long-lasting alterations in stressinduced phenotypic plasticity related to asthma risk. 46 There are frequent reports that nonwhite children living in poverty and residing in urban areas have a significantly higher risk of asthma than white children.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large health inequalities in this area social stressors have been used extensively to explain racial disparities in childhood asthma 20 . Indeed recent research suggests that the social context children are raised in may be equal to the natural environmental effects in asthma disease risk 21 .…”
Section: Social Determinants Of Child Healthmentioning
confidence: 99%
“…Many studies have separately demonstrated that environmental contaminants like air pollution and metals as well as early-life social and psychosocial factors, such as living in poverty and experiences of adversity, have independent and substantial effects on a range of child health outcomes including asthma, cognition and behavior, obesity, and perinatal risks like being born low birth weight [2][3][4][5]. Fewer studies have considered explicitly the accumulation of risk and potential synergies between social and environmental risks as determinants of child health outcomes.…”
Section: Introductionmentioning
confidence: 99%